URGENSI BIMBINGAN ORANG TUA DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK PADA KELUARGA PETANI (STUDI PADA DUA MI DI DESA BAGIK PAYUNG) - Bisyrulhafy; Saharudin; Siti Rapipah (Al-mujahidah, 2021)
This study examines the urgency of parental guidance in enhancing students' learning motivation in farming families, specifically in two Madrasah Ibtidaiyah (MI) in Bagik Payung Village. Farming families often face economic and educational challenges that affect their children's learning motivation. The purpose of this research is to identify the role of parental guidance in increasing students' learning motivation within farming families. This research employs a qualitative descriptive method with a case study approach. Data collection techniques include in-depth interviews, participatory observation, and documentation. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results of the study indicate that parental guidance plays a significant role in enhancing students' learning motivation. Parents who actively guide their children, despite limited resources, can encourage them to perform better in school. The conclusion of this research underscores the importance of parents' roles in their children's education, especially among farming families. The implications of this study include recommendations for schools and the government to increase parental involvement in education to support students' learning motivation.